Pengadaan Tanah Untuk Kepentingan Umum Diatas Tanah Wakaf (Studi Kasus Proyek Jalan Tol Di Musholla Qubatul Jannah Desa Adiwerna Kecamatan Adiwerna Kabupaten Tegal) - Muhamad Fahmi; Evy Indriasari; Bha’iq Roza Rakhmatullah (Jurnal I-Philanthropy, 2024)
The provision of land in the development process is referred to in law as land acquisition. This land acquisition process generally involves property owned by various parties, including waqf land. In the construction of the Trans Java Toll Road in Central Java Province, there are 85 waqf lands, including 9 waqf lands in Tegal Regency, one of which is the Qubatul Jannah mosque in Adiwerna Village, Adiwerna District, Tegal Regency. This study aims to examine the existing legal regulations in Indonesia regarding waqf land affected by land acquisition for toll road construction at Qubatul Jannah musala To examine the procedures for waqf land affected by land acquisition for construction of toll roads for public purposes at Qubatul Jannah musala in Adiwerna Village. The type of research is library research. The approach used is a case approach in normative research. Data collection techniques through literature studies, interviews and qualitative data analysis. The results showed that the regulation of waqf land affected by land acquisition for the construction of the Qubatul Jannah mosque toll road in Adiwerna Village refers to Law Number 41 of 2004 concerning Waqf jo. Government Regulation Number 25 of 2018 concerning Amendments to Government Regulation Number 42 of 2006 concerning the Implementation of Law Number 41 of 2004 concerning Waqf. And for the procedure, the nadzir must submit an application for a permit to change the status of the exchange of waqf land to the Ministry of Religion of Tegal Regency which has been equipped with a waqf land valuation document. Based on the results of this research is expected to be information and input for students, academics, practitioners and all parties in need within the Faculty of Law, Pancasakti University Tegal.